2009
DOI: 10.1111/j.1651-2227.2009.01365.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of individualized weight‐loss programmes on adiponectin, leptin and resistin levels in obese adolescent boys

Abstract: In obese adolescents boys, moderate exercise training completed at Lipox(max) and combined with energy restriction improves their ability to oxidize lipids, which is associated with a normalization of their adiponectin, leptin and resistin levels resulting in an improved insulin sensitivity, as attested by a higher ALR and a lower HOMA-IR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
77
2
9

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(98 citation statements)
references
References 28 publications
10
77
2
9
Order By: Relevance
“…The PE program was unable to increase TA values in any of the groups, contrarily to other studies (22). TA and adiponectin multimers seem to require marked reductions in adiposity to improve.…”
Section: Longitudinal Studycontrasting
confidence: 39%
See 1 more Smart Citation
“…The PE program was unable to increase TA values in any of the groups, contrarily to other studies (22). TA and adiponectin multimers seem to require marked reductions in adiposity to improve.…”
Section: Longitudinal Studycontrasting
confidence: 39%
“…Contrarily, another study found no impact on TA levels after a nutritional counseling program in prepubertal Portuguese children, despite the improvement in BMI z-score (BMIzsc) and blood lipids (21). Different results were found in a study involving obese adolescent boys, as improvements in adiponectin levels were obtained both by energy restriction and by exercise separately, moreover, cumulative effects were present when both approaches were combined (22).…”
mentioning
confidence: 88%
“…We focused our attention on adiponectin, and we found that the highest circulating levels of this adipocytokine were found in the underweight groups of teens. This observation is consistent with the previously described effects of weight-loss on increases in serum adiponectin (Elloumi et al, 2009). Interestingly, high levels of serum adiponectin have been reported in anorectic patients (Nedvidkova et al, 2005;Pannacciulli et al, 2003).…”
Section: Discussionsupporting
confidence: 82%
“…On the basis of the crossover concept, 11 several studies have individualized and calibrated the intensity of exercise training at LIPOXmax and showed that this type of training is efficient for contracting the metabolic dysfunction-related obesity, consequently leading to better lipid oxidation during exercise, as well as body composition and insulin sensitivity improvement in obese children. 6,10,12 The assessment of functional capacity and exercise tolerance is commonly examined in obese subjects by cardiopulmonary exercise test with measurement of respiratory gas exchange, which requires sophisticated equipment and specially trained personnel. Although the cardiopulmonary exercise test remains the gold-standard method of assessing the individual's metabolic, cardio-respiratory fitness and maximal capacity for exercise, the high-intensity nature of exhaustive stress tests may be inappropriate for certain low-fit or patient groups.…”
Section: Introductionmentioning
confidence: 99%